on from Japanese to Spanish: Considerations from a Cognitive and Cultural Approach to Linguistics - Montaner Montava, Mª Amparo (Estudios de Traducción, 2012)
Translation Studies require a wide conception of Linguistics, which considers Cognition and Culture as a tool in the communication process. From this point of view, the first section of this paper includes several considerations that a translator should bear in mind in order to work with languages that are not typologically and culturally related, such as Japanese and Spanish. The last section discusses some linguistic problems of literary translation, analysing examples of tanslation of poetry.
Keywords: problem; translation; linguistics; literature; Spanish; Japanese.